Valor nutritivo de silagens de grãos de milho puro ou com adição de grãos de soja, de girassol ou uréia avaliado em cordeiros - Lombardi, Lausimery (2007)
This work objective to evaluate the chemical composition and aerobic estability of corn grains silages added with crude soybean, sunflower or urea. The following treatments arranged in a completely randomized design with four replications were evaluated: corn grain; corn grain + soybean; corn grain + sunflower grain and corn grain + urea. Plastic barrels were used as experimental silo with a capacity off about 200 kg, and kept closed for nine months. It was evaluated the chemical composition, dry matter and crude protein ruminal degradability and starch ruminal disappearance. Also it was evaluated the aerobic estability of silages. It was observed the addition effect of soybean, sunflower or urea on silages chemical composition especially on dry matter and ether extract content. Therefore there was effect on dry matter and crude protein effective degradability. The silage with higher aerobic stability was corn + urea silage. It was concluded was that the addition of soybean, sunflower or urea in corn grain silages result in chemical composition improvement.